2019
DOI: 10.3390/medicina55030077
|View full text |Cite
|
Sign up to set email alerts
|

Energy Expenditure of a Single Sit-to-Stand Movement with Slow Versus Normal Speed Using the Different Frequency Accumulation Method

Abstract: Background and objectives: The purpose of this study was to compare the energy expenditures (EE) of a single sit-to-stand (STS) movements with slow and normal speeds using a multi-stage exercise test. Materials and Methods: Twelve young males, aged 21–27 years (age, 23.0 ± 1.7 years; height, 171.2 ± 6.1 cm; weight, 64.3 ± 5.6 kg), performed repeated 3-s stand-up and 3-s sit-down (slow) or 1-s stand-up and 1-s sit-down (normal) movement on two different days with random order. All the participants completed mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…When the speed was slow (3 s), the energy cost increased by 40%. Moreover, when the body weight increased, the intensity of sit-to-stand transitions increased as well [26]. These findings may help us to understand why OW or obese people are reluctant to stand up.…”
Section: Resultsmentioning
confidence: 81%
“…When the speed was slow (3 s), the energy cost increased by 40%. Moreover, when the body weight increased, the intensity of sit-to-stand transitions increased as well [26]. These findings may help us to understand why OW or obese people are reluctant to stand up.…”
Section: Resultsmentioning
confidence: 81%
“…The 6MWT is already validated for young people and it is the most commonest for assessing the functional capacity in clinical setting but, it has troublesome logistical requirements such as 30 meter corridor and it is time consuming and occasionally it may be difficult to test the individuals with severely limited mobility with the 6MWT but STS test requires minimal equipment and it's easy to perform [16]. The STS test is a measure of mobility related function and physical performance [17]. A slow STS activity requires 4.5 METs for frequency of 10 times/min similarly walking 5.6 km/hr utilizes 4.5 METs therefore STS activity can be performed instead of walking but further studies should be conducted regarding same [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Our data show that patients with CRF have nearly 38.1% fewer sit-to-stand transitions than patients without CRF. A potential explanation why people with CRF have fewer sit to stand transitions is the need for energy conservation, because patients require more energy expenditure to move from sit-to-standing posture [62]. Studies have shown that cancer survivors do more passive leisure pursuits [63].…”
Section: Fatigue and Posturementioning
confidence: 99%